Assessment of quality of life and changes in intestinal microbiota in patients with rheumatoid arthritis - Mikulets, Liudmyla; Glubochenko, Olena; Bobkovych, Katerina; Ivanitsky, Anton (ScienceRise: Medical Science, 2017)
Aim. The aim of the work was to study life quality indices depending of degrees of large intestine microflora in patients with rheumatoid arthritis. Methods. The study was carried out on 43 patients with rheumatoid arthritis and 21 practically healthy persons. To determine the role of intestinal microflora in the rheumatoid genesis in patients with RA, excrements microbiological study was carried out. The comparative assessment of life quality parameters was carried out using SF-36 questionnaire. Result. In all patients with RA were extracted bifidobacteria, lactobacteria, bacteroides and colon bacillus, at that eubacteria, peptococcus and enterococci were eliminated from their large intestine cavity. On this background the contamination of the large intestine cavity by pathogenic and conventionally pathogenic enterobacteria and also Clostridium bacteria, staphylococci and Candida yeast-like fungi took place. The analysis of SF-36 questionnaire scales demonstrated that all parameters of patients with RA were lower than in the control group and depended on large intestine cavity microflora changes by certain indices. Conclusions. In patients with rheumatoid arthritis is observed the change of specific and population level of large intestine cavity microbiota. At dysbiotic disorders in these patients was observed the decrease of life quality indices, especially, ones of the physical health component. The lowest life quality indices were observed in patients with ІІІ degree of microbiological disorders